Effect Of Tax Knowledge On Individual Taxpayers Compliance - Damajanti, Anita; Karim, Abdul (Universitas Semarang, 2017)
Indonesia uses self-assessment system in income tax collection. This system requires the taxpayer to understand the method of calculating payments and tax reporting in accordance with applicable regulations. The problem faced by many taxpayers who do not understand the tax laws. Taxpayers who do not understand tax law become an obstacle for the implementation of self-assessment system in the collection of income tax. This study will examine empirically the influence of tax knowledge on tax compliance of individuals enrolled in the Tax Office (KPP) Central Java Region I. This study develops previous studies that have been carried out in Indonesia by separating variable tax knowledge into 3 (three) variables i.e. knowledge of tax reporting, tax calculation knowledge, and knowledge of tax payments.Data were collected using a questionnaire that is sent directly to the taxpayer. Questionnaires were sent as many as 200 copies. A total of 196 copies of the completed and can be processed. The test results indicate that the instruments used in this study are valid and reliable. Results of hypothesis testing using regression provides empirical evidence that knowledge of tax reporting, tax calculation and knowledge of tax payments significant effect on tax compliance.